When private internal investigators turn against the whistleblower: The case of Norwegian police - Gottschalk, Petter (International journal of police science & management, 2017)
The work of fraud examiners in private internal investigations is important to many auditing and law firms. They are hired by public and private organizations when there are suspicions of misconduct and financial crime. Such suspicions are sometimes disclosed by whistleblowers who attempt to disclose practices that they perceive as illegal, immoral or illegitimate. This article presents a case from the Norwegian police in which whistleblowers expressed concerns about overtime, use of private cars, and the procurement of equipment for personal use. The main whistleblower was also the ombudsman within the organization, where he repeated his accusations and allegations so frequently that he became the main subject of the private internal investigation. This study finds some support for the blame game hypothesis.